Support and Reluctance in the Pre‐substantive Phase of Alleged Child Abuse Victim Investigative Interviews: Revised versus Standard NICHD Protocols. (24th November 2014) - Ahern, Elizabeth C.; Hershkowitz, Irit; Lamb, Michael E.; Blasbalg, Uri; Winstanley, Alice; Hobbs, Sue D.; Goodman, Gail S.
<x xml:space="preserve">Abstract</x> Children's unwillingness to report abuse places them at risk for re‐victimization, and interviewers who do not respond sensitively to that unwillingness may increase the likelihood that victims will not disclose abuse. Interviewer support and children's reluctance were examined on a turn‐by‐turn basis using sequential analyses in 199 forensic interviews of 3‐ to 13‐year‐olds who alleged maltreatment. Half of the children were interviewed using the Revised Protocol that emphasized rapport‐building (RP), the others using the Standard National Institute of Child Health and Human Development Protocol (SP). When using the RP, interviewers provided proportionally more support than when using the SP, but even when using the RP they did not specifically provide support when children expressed reluctance. The RP promoted immediate cooperation when reluctant utterances were met with support, however, suggesting that supportive statements were valuable. The findings enhance our understanding of children's willingness to participate in investigative interviews and the means through which interviewers can foster the comfort and well‐being of young witnesses. Copyright © 2014 John Wiley & Sons, Ltd.